An Analysis of Pronunciation Errors Made By Indonesian Singers in Singing English Song on Youtube - Murti Bandung; Syamsuriyana Muchlas (Humanitatis : Journal of Language and Literature, 2020)
This research was aimed to know the errors of pronunciation made by Indonesian singers in singing English song on YouTube. The subjects are singers in the age range of 18 to 25 years old. The researcher found 4 Indonesian singers on YouTube which are famous and have a good voice. This research used qualitative method. To collect the data, the researcher searched an American singer on Google, then found a good song and the lyrics on YouTube. Listen to the original music several times and then try to find the Indonesian singers who covered the same song, the last is listen to their singing and analyze it. The researcher found 14 words that were mispronounced by the Indonesian singers on their YouTube channel. There were 8 consonants, they were /θ/,/ð/, /dӡ/, /d/, /v/, /c/, /s/, /p/, and 2 vowels that mispronounced by them, They were /ɪ/, and /æ/. There were several causes that affect their pronunciation. In this research, the researcher hopes that this research can make the singers, students, teachers, etc, to improve their pronunciation skill.